Analisis kepatuhan syariah (Sharia compliance) dalam implementasi pembiayaan pada KSPPS BMT Indragiri cabang Pasir Pengaraian - Syukri Rosadi; Rozi Andrini (AL-Muqayyad, 2026)
This study aims to analyze the level of sharia compliance in the implementation of financing and to identify the factors influencing the application of sharia principles at the Islamic Savings and Financing Cooperative BMT Indragiri Branch Pasir Pengaraian. This research employs a qualitative approach using a field research method. Data were collected through interviews, observations, and documentation involving 25 informants consisting of the cooperative chairman, BMT management, financing members, and surrounding community members. The data analysis technique used the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The results indicate that financing implementation has applied sharia contracts such as murabaha, mudharabah, and musyarakah, supported by clear and transparent contract documentation. However, members’ understanding of sharia contract concepts remains limited. Influencing factors include human resource competence, sharia supervision systems, sharia financial literacy, and institutional support. Therefore, strengthening literacy and supervision is necessary to ensure optimal and sustainable sharia compliance implementation.